IN-VITRO ANTHELMINTIC ACTIVITY OF OLEANDRA MUSIFOLIA (BL.) PRESL. AGAINST HAEMONCHUS CONTORTUS (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Ethanolic, aqueous and Petroleum ether extracts from the whole fern, Oleandra musifolia (Bl.) Presl. (Family-Oleandraceae) was investigated for anthelmintic activity against Haemonchus contortus, with varied drug concentration (25, 50, and 100) mg/ml and the time taken for paralysis and death of the worm was determined. The in-vitro anthelmintic activity was compared with standard reference drug Albendazole and control distilled water. The result showed ethanolic extract performed well to express the anthelmintic efficacy than aqueous and petroleum ether extracts and the standard Albendazole. However efficacy is better and directly proportional to the increase in varied drug concentration. The efficacy is determined as lesser time taken to cause paralysis and death of Haemonchus contortus as compared to standard reference drug.